2013
DOI: 10.1007/s10620-013-2858-8
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-92a Functions as an Oncogene in Colorectal Cancer by Targeting PTEN

Abstract: Our results demonstrated that miR-92a induced EMT and regulated cell growth, migration and invasion in the SW480 cells, at least partially, via suppression of PTEN expression. MiR-92a may serve as a novel therapeutic target in colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
86
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 30 publications
5
86
0
Order By: Relevance
“…However, other studies demonstrated that miR-92a expression is upregulated in several cancers and functions as oncogene and plays a critical role in cancer development. For example, Zhang et al reported that miR-92a induced EMT and regulated cell growth, migration, and invasion in the colorectal cancer cells, at least in part, via suppression of PTEN expression [28]. Chen et al found that miR-92a expression was increased in esophageal squamous cell carcinoma (ESCC), and its expression was significantly associated with the lymph node metastasis and TNM stage in ESCC patients and promoted the migration and invasion of ESCC cells via targeting CDH1 [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies demonstrated that miR-92a expression is upregulated in several cancers and functions as oncogene and plays a critical role in cancer development. For example, Zhang et al reported that miR-92a induced EMT and regulated cell growth, migration, and invasion in the colorectal cancer cells, at least in part, via suppression of PTEN expression [28]. Chen et al found that miR-92a expression was increased in esophageal squamous cell carcinoma (ESCC), and its expression was significantly associated with the lymph node metastasis and TNM stage in ESCC patients and promoted the migration and invasion of ESCC cells via targeting CDH1 [29].…”
Section: Discussionmentioning
confidence: 99%
“…This agreed with Faltejskova et al [33] who documented evidence against using it in diagnosing and monitoring CRC, contrary to many studies that confirmed its significant role in diagnosing CRC with adequate sensitivity and specificity [11,34,[37][38][39]. Even Huang et al ascertained its role when combined with miR-29a [34].…”
Section: Discussionsupporting
confidence: 73%
“…miR-29a promoted CRC and its metastasis by regulating matrix metalloproteinase and E-cadherin, through its direct targeting KLF4 [9], the identified tumour suppressor gene involved in cell proliferation, migration and invasion [10]. Similarly, miR92a, which was upregulated in CRC, stimulated epithelial to mesenchymal transition, with negative influence on phosphatase and tensin homologue lucoferase activity [11]. On the contrary, miRNA-145 was downregulated in most primary CRC, particularly the aggressive forms, via targeting fascin-1 [12], elementary in neoangiogenesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…The aberrant expression of many miRNAs has been linked to human diseases including cancers. 7 To date, multiple cellular miRNAs, such as miR-148a, 8 miR-155, 9 miR-377, 10 miR-92a, 11 miR-200c, 12 miR-23a, 13 miR-130b, 14 miR-30a, 15 miR-149 16 and miR-93 17 have been reported to modulate the EMT and metastasis in various cancers, but only three of them are implicated in the EMT in nasopharyngeal carcinoma (NPC), a malignancy typically featured by its early metastasis and invasion. [17][18][19] Therefore, it is necessary to identify other unknown miRNAs that regulate the EMT and metastasis of NPC cells.…”
Section: Introductionmentioning
confidence: 99%